The Effect Of Service Quality And Destination Image On Return Visit Intention Through Tourist Satisfaction - Sumarni, Iseu; Baskara, Ika; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to determine how service quality and destination image affect revisit intention by considering satisfaction as mediation. This research uses quantitative methods, with data collection techniques in the form of surveys, by distributing questionnaires to respondents online. This study successfully collected a sample of 100 respondents and analyzed using Structural Equation Modeling (SEM) with a variant or component-based approach with Partial Least Square (PLS). The results prove that all relationships have a positive effect, including the mediating role of tourist satisfaction in the indirect effect between service quality and revisit intention and the mediating role of tourist satisfaction in the indirect effect between destination image and revisit intention. This managerial implication can be used as a reference material to increase the intention to visit again by creating a marketing strategy, implementing several new policies, to optimize the role of satisfaction as a mediator so that tourism managers can maintain quality service, and a pleasant experience through destination image, according to what consumers want and expect. Keywords: Image Destination, Revisit Intention, Service Quality, Tourist Satisfaction.